The simulation and experimental validation of a novel noninvasive multi-target electrical stimulation method - Kai Zhu; Xiaoqing Zhou; Xu Liu; Ren Ma; Mingpeng Wang; Shunqi Zhang; Tao Yin; Zhipeng Liu (Scientific Reports)
Abstract The brain is a complex system of structure and function. Brain diseases and brain functional abnormalities often involve multiple functionally connected regions, including the deep brain. Studies have shown that multi-target electrical stimulation is more effective than single-target electrical stimulation. However, non-invasive multi-target electromagnetic stimulation, such as multi-target transcranial magnetic stimulation (TMS), transcranial direct current stimulation (tDCS) and transcranial alternating current stimulation (tACS) cannot meet the needs of synchronous multi-target accurate electrical stimulation at the deep brain. In this paper, based on the principle of magneto-acoustic coupling and phased array focusing technology, a novel non-invasive multi-target transcranial magneto-acoustic coupling electrical stimulation (multi-target TMAES) method is proposed. A simulation model and experimental system were established. The simulation and experimental results proved that the proposed multi-target TMAES can non-invasively achieve precise focused electrical stimulation of two targets. The average focal point size of each target is 5.1 mm. The location and intensity of the multi-target electrical stimulation can be flexibly changed by adjusting the system parameters according to the actual need. It will provide a new and promising tool for the treatment of brain diseases and the study of neural circuits and brain functional connectivity.